The Effect Of Nitrogen Fertilizers Of Various Rates On The Yield Of Fine-Fiber Cotton - Kh.Kh.Zokirov; M.T.Ne'matova (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Cotton growing is one of the main industries of our country, satisfying the need of humanity for the only natural cellulose. For this reason, on March 6, 2020, the President of the Republic of Uzbekistan Sh.M.Mirziyoyev adopted Resolution No. PQ-4633 “On the widespread introduction of market principles in the field of cotton growing”. It states that updating and placing cotton varieties in agricultural production in Uzbekistan, properly organizing their selection and seed production, achieving fiber quality at a competitive level in the world market, effective use of mineral fertilizers, and absolutely preventing the monopoly of cotton are important tasks set before the cotton growers of our country. In this regard, the agrophysical and agrochemical properties of the experimental fields were studied, and on this basis, the effect of different rates of nitrogen fertilizers on the yield of Termez-208 fine-fiber cotton was studied. According to the results of the experiment, an annual rate of nitrogen fertilizers was recommended for fields with low nitrogen and phosphorus and sufficient potassium, distributed on the barren meadow soils of the Surkhandarya region.